Using mobile phone applications in engaging nurses for preventing healthcare-associated infections: A systematic review - Yayu Nidaul Fithriyyah; Khudazi Aulawi (Tehran University of Medical Sciences, 2021)
Background & Aim: Prevention of healthcare-associated infections targets health workers. Considering the crucial role of nurses, potential applications of mobile phone-based interventions are innovative, attractive, and easily accessible. This study synthesizes mobile applications with the involvement of nurses or nursing students in outcomes to prevent healthcare-associated infections and their implications. Methods & Materials: Systematic review, database searches included: SCOPUS, EBSCO MEDLINE, PubMed, ProQuest, Institute of Electrical and Electronics Engineers, and SagePUb. Population involved nurses or nursing students with mobile-based interventions about healthcare-associated infectionsQuantitative design focused on publications between 2015-2021. Methodological quality applied the Cochrane and the National Heart, Lung, and Blood Institute tools. Analysis used narrative synthesis. Results: 11 studies met inclusion criteria from 1,792. Study populations were heterogeneous. Mobile phone interventions included: short message service (18.2%), (9.1%), mobile and computer access (18.2%), and iOs/Android-based (27.3%). healthcare-associated infections prevention focused on: surgical site infections (54.5%), central line-associated bloodstream infections (9.1%), catheter-associated urinary tract infections (9.1%), antimicrobials (9.1%), knowledge, attitude, and practice towards healthcare-associated infections (18.2%). Most bias risks were moderate to high. Participants showed positive responses. All studies described problems in implementing healthcare-associated infections applications. Five studies reported estimated cost savings. Conclusion: Using mobile phone applications has involved nurses as researchers, participants, and intervention providers to patients. The impact is promising in preventing healthcare-associated infections. Response of user is influenced by technology familiarity, which involves interactive features and problem anticipation. This review showed significant cost savings, so stakeholders and future research plans can consider it.